An investigation into assertives in presidents’ welcome messages on official websites of colleges and universities in the usa - Đoàn,Thị Hồng Nguyễn (ĐHĐN., 2015)
Based on the theories of Speech Acts, this paper aims to investigate assertives in Presidents’ Welcome Messages (PWMs) in an attempt to discover their striking linguistic features in terms of lexical, syntactic and semantic aspects. The method design in the study is qualitative and quantitative combined approach which includes descriptive and inductive methods. The researcher has chosen fifty welcome messages ranged from 200 to 400 words for the study. The sample of an assertive speech act in PWMs is a sentence or a sequence of sentences which convey information about some state of affairs of the world (i.e.tertiary institutions) from the writer (i.e. presidents) to the reader (i.e. perspective learners) to cause some kind of action. Yule [1996] classified representatives or assertives into four types namely statements of fact, assertions, conclusions as well as descriptions. The findings also aim at suggesting some implications for teaching English to Vietnamese learners, especially who are interested in the writing skill. As regards, the findings, in terms of lexical features, assertives consist of a great deal of adjectives and noun phrases to describe the institution strengths. Mottos are also commonly used in these assertives with a wide range of patterns. In terms of syntactic features, the active voice outnumbers the passive voice in this type of discourse. Furthermore, the complex and simple sentences in active forms occur far more frequently than compound and compound-complex sentences. Particularly, parallel structures are used to emphasize the training and research capability of the colleges and universities. With regard to semantic features, there exist four types of assertives in PWMs: assertion, description, statements of fact and conclusion